2007 3rd International IEEE/EMBS Conference on Neural Engineering 2007
DOI: 10.1109/cne.2007.369721
|View full text |Cite
|
Sign up to set email alerts
|

Application of Optimization Methods to Predict Performance of a Vibrotactile Balance Prosthesis

Abstract: System identification and modeling methods were employed to investigate how subjects use orientation information provided by a vibrotactile balance prosthesis. Previous results showed systematic, frequency-dependent changes in the dynamic responses to postural perturbations due to surface tilts as a function of prosthesis feedback parameters. These results could be modeled by a relatively simple feedback control model with the contribution from the prosthesis feedback being dependent on the relative proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In a separate study, we investigated whether it was possible to predict this pattern of G Tactor changes as a function of the prosthesis feedback conditions [24]. We hypothesized that systematic changes in G Tactor were related to the optimization of a performance goal with G Tactor changes predicted by minimizing a cost function.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, we investigated whether it was possible to predict this pattern of G Tactor changes as a function of the prosthesis feedback conditions [24]. We hypothesized that systematic changes in G Tactor were related to the optimization of a performance goal with G Tactor changes predicted by minimizing a cost function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the model indicated that reliance on the vibrotactile feedback was highly dependent on the type of information encoded: participants relied upon the vibrotactile feedback more when it encoded body sway angle compared to sway velocity. A related study was able to predict how reliance changed with different combinations of angular position and velocity feedback by assuming participants optimally used augmented feedback to minimize a linear combination of sway angular position and jerk (the third derivative of displacement) ( 90 ).…”
Section: Sensory Augmentation Assessment Using Balance Modelsmentioning
confidence: 99%